(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article discusses the erasure and the exclusion of female stage technicians in Brazilian theatrical productions, as well as the sexual divisions present in the stages of the production line of this craft. For this, we dialogue with theoretical and methodological concepts of authors of feminist thought who contribute to the guided speeches: Perrot (1998), Spivak (2010) and Kilomba (2019). Through documental analysis, we point out the effective participation of women scenographic technicians and the division of labor present in the stages of scenographic production.